Unlocking Engagement: The Power of Gamification in Anatomy Education - Hudebia Allah Buksh, Maryam Waqar Panhwar, Pashmina Shaikh, Sana Kashif (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Although a foundational aspect of medical pedagogy, the teaching of anatomy is frequently regarded as tedious in traditional formats. An alternative potential method of improving engagement is the implementation of gamification, which utilizes various components of play, competition, and reward structures. This study evaluated the impact of gamified learning on knowledge acquisition, motivation, and satisfaction among first- and second-year MBBS students enrolled in anatomy courses. Methodology: This research was conducted as a quasi-experimental study and was undertaken at Liaquat University of Medical and Health Sciences (LUMHS), Jamshoro, and Khairpur Medical College from January to July 2023. Two hundred MBBS students participated in the study. Anatomy was taught using three gamified modules which included pedagogical quizzes, puzzles, and interactive point systems which included a feedback mechanism, leaderboards, and gamification of feedback in real time. Knowledge was evaluated with pre and post-tests and a Likert scale questionnaire was used to assess the students’ engagement, confidence, and satisfaction. Descriptive and inferential statistics were used to analyze the data with a confidence interval of 95% (p < 0.05). Results: Gamification led to significant improvement in learning outcomes. The mean knowledge score increased from 54.1 ± 9.6 (pre-test) to 78.4 ± 8.3 (post-test) (p < 0.001). Confidence, engagement, and satisfaction scores also showed notable increases. No significant gender difference was observed in learning gains (p = 0.412). A strong positive correlation was noted between engagement and knowledge improvement (r = 0.66, p < 0.001). Overall, students demonstrated high satisfaction with gamified learning and reported increased motivation and enjoyment in anatomy sessions. Conclusion: Incorporating aspects of gamification into the teaching of anatomy positively improved knowledge acquisition, motivation, and engagement of MBBS students. Adopting an interactive and enjoyable approach to what is often considered an unengaging and rote learning discipline showcases the potential of gamification to positively enhance students’ participations and performance. The introduction of deliberate gamified elements into the medical undergraduate curriculum would provide the opportunity for more engaging and student-centered learning environments. Keywords: Gamification; Anatomy Education; Medical Students; Learning Motivation; Educational Innovation; Engagement; Interactive Learning.